[US Soldiers at Army Barracks, World War II Chaguaramas] - (:unkn) unknown (My University, 2010)
This is a photograph of United States soldiers at army barracks. The architecture of the barracks appears to have a Spanish influence. The soldiers are clad in white shirts and pants, sailor-type hats and neck ties. The landscape is barren.
Colour: Sepia; Style: Landscape; Other: Bordered; Divided
Keywords: Trinidad and Tobago; Postcards; Military uniforms; Soldiers--United States; Armed Forces; Barracks; Cities and towns--Chaguaramas